WirelessHART Routing Analysis Software - Winter, Jean; Lima, Carolina; Muller, Ivan; Pereira, Carlos; C. Netto, João (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2011)
Reliability and robustness are critical parameters in choosing a wireless protocol to be used in industry. Nowadays, WirelessHART is the most adopted wireless industrial protocol. However, there are only a few number of analysis tools for industrial networks, specially for WirelesHART, which implies in a lack of information about the health network to its end users. In this paper a software to obtain network data from a WirelessHART network is presented. The developed software allows to identify relevant issues to the verification and maintenance of WirelessHART networks. One of the advantages is the ability to customize the tests, being allowed to evaluate data of most interest for a particular purpose. In a case study, the obtained data allowed to identify the mostly used routes of the network which lead to the identification of bottlenecks.